Quranic Principles for the Fears and Dangers of Human Life and Their Prevention: انسانی زندگی کے خوف و خطرات اور ان سے بچاؤ کے قرآنی اصول حیات - Dr. Muhammad Naeem Anwar; Muhammad Azeem (Al-Asr International Research Journal of Islamic Studies, 2024)
Undoubtedly, human life in its natural state is sometimes overcome by sadness, at times by weariness, and occasionally by anxiety over a matter. Sometimes, worry about a problem takes hold, or an overwhelming sense of urgency dominates. Fear of something may become a persistent feeling, or a physical illness may turn terrifying. A relationship may become a source of distress, or an internal struggle may transform into an external trial. At times, the imbalance and discord in human relations become a headache. Occasionally, the betrayal of loved ones becomes unbearable. All these things combine to create in a person an overwhelming sense of fear, sorrow, grief, and anguish. Yet, this very fear, in its positive aspects, can become a transformative and invaluable asset—especially when a person keeps before them the teachings of Allah Almighty and His Messenger (peace be upon him). Then, neither grief remains grief, nor fear remains fear. Instead, these very emotions become a source of tranquility in this world and the Hereafter."